Trends and Development in Enteral Nutrition Application for Ventilator Associated Pneumonia: A Scientometric Research Study (1996–2018) - Chen, Shengqi; Bie, Ruixue; Lai, Yunfeng; Shi, Honghao; Ung, Carolina Oi Lam; Hu, Hao (Frontiers in Pharmacology, 2019)
Background: This study aimed to explore the intellectual landscape of the studies about the clinical application of enteral nutrition (EN) in patients with ventilator associated pneumonia (VAP), and to identify thematic development trends and research frontiers in this area. Methods: Scientometric research was conducted by analyzing bibliographic records retrieved from the Web of Science Core Collection Database dated between 1996 and 2018. Reference co-citation analysis, key words co-occurrence analysis and cooperation network analysis were performed using CiteSpace software. Results: A total of 124 valid records were included in the final dataset. It was found that early studies were mainly focused on the feeding pathways of EN among VAP patients. The risks associated with EN intervention in VAP patients including gastric nutrition intolerance and aspiration pneumonia were extensively investigated and reported. While aspiration pneumonia has remained a long-term active research area in the field of EN interventions for VAP patients, with recent research focused more on interventions aiming to improve EN support and to optimize the use of EN for VAP patients. It seems that clinical guideline on EN interventions for VAP patients need to be established. Conclusion: The advantages of EN for VAP patients have been recognized but still require further investigation on standardizing the use. Strategic cooperation among hospital physicians, university researchers and industrial product developers is needed to establish clinical guideline and continue to develop innovative EN products to tackle VAP.